Perancangan Aplikasi Mobil Derek Berbasis Android Menggunakan Metode Scrum - Kukuh Primadito Raharjo; Gita Fadila Fitriana; Novian Adi Prasetyo (Jurnal Informatika Global)
Transportation is one of the facilities in an area to improve accessibility or the relationship of an area because accessibility is often associated with the area. The Central Bureau of Statistics explained that the increase in motorized vehicles in 2015 - 2019 was a significant increase of 6.13%. Under the high demand for mobility, there may be barriers that impede this mobility. The problem with the vehicle used is due to engine damage. To overcome this problem, one solution is to call a tow truck. A tow truck is a vehicle that is used to tow a vehicle that has a traffic accident that is unable to move on its own. In the use of tow trucks, there are still problems experienced by customers and tow truck drivers, namely it is difficult to find the position of the customer's whereabouts with information or addresses that are not necessarily accurate for tow truck drivers and the lack of information about the nearest tow truck for customers. By using the Scrum method, this tow truck search application is designed to be able to place orders by displaying maps to find out the pick-up point, destination point, and tow truck location and can display the availability of tow trucks around the customer. Testing on this application is carried out using Black Box to obtain a percentage of eligibility results of 99.16% and System Usability Scale (SUS) gets an average value of 76.6 these results in SUS getting a grade B percentile rank score. Keywords : Tow Car, Scrum, Android, SUS, Black Box